Mechanically activated kaolin modified fly ash phosphoric acid-based geopolymer and preparation method thereof
By mechanically activating the method of polymer polymers of the alpine coal and coal phosphate base, the problem of insufficient early intensity of polymer polymers at the ash base is solved, and high pressure and durability are realized, and energy consumption and carbon emissions are reduced.
Patent Information
- Application Number
- CN202411422807.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Fly ash-based acid-excited polymers have shortcomings in early strength and preparation, limiting their widespread use in structural applications.
Mechanically activated kaolin is used to modify fly ash phosphate-based polymers. By using solid waste materials such as fly ash, red mud and mechanically activated kaolin as precursors, combined with surface modifiers and acid initiators, the interaction between geopolymers is optimized. Function and structure.
It significantly improves the early and long -term pressure resistance of the ground polymer, enhances its durability and structural stability, and reduces energy consumption and carbon emissions, and realizes the use of solid waste resource.
Smart Images

Figure CN119349932A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a mechanically activated kaolin-modified fly ash phosphate-based polymer and a preparation method thereof. Background Art
[0002] Geopolymer is a cementitious material synthesized by chemically activating precursor materials. It is widely used in civil engineering, such as road construction, foundation reinforcement and environmental remediation. This type of material is favored for its excellent mechanical properties, excellent durability and environmental adaptability. The precursor of traditional geopolymer is mainly kaolin, but with the demand for sustainable development, many experts and scholars have begun to explore the use of solid waste materials such as slag, granite powder and coal gangue as alternatives. Although acid-activated geopolymers show faster hardening speed and better weather resistance than alkali-activated materials, fly ash-based acid-activated geopolymers still have deficiencies in early strength and preparation process, which limits their widespread use in structural applications.
[0003] In current technology, fly ash is a byproduct of coal-fired power plants with an annual output of up to 500 million tons worldwide. Although it is rich in useful components such as silicates, aluminates and iron oxides, it is theoretically suitable for the production of geopolymers. However, acid-activated geopolymers based on fly ash are usually difficult to meet engineering requirements due to insufficient mechanical strength. This is mainly due to the failure to effectively promote the full reaction of active components in fly ash during the acid activation process and the uneven microstructure of the material that may be caused by the acid activation system. Summary of the invention
[0004] The purpose of the present invention is to propose a mechanically activated kaolin-modified fly ash phosphate-based polymer and a preparation method thereof, which increases the early strength, long-term strength, durability and economy of the polymer while ensuring the large-scale consumption of bulk solid wastes such as fly ash and red mud, and reduces the energy consumption and carbon emission problems caused by calcined kaolin, making it better suitable for various civil engineering projects such as road construction, foundation reinforcement, and environmental remediation.
[0005] In order to achieve the above purpose, this application adopts the following technical solutions:
[0006] In the first aspect, the present invention provides a mechanically activated kaolin-modified fly ash phosphate-based geopolymer, wherein the geopolymer is made of the following raw materials in parts by weight: 30 to 75 parts of fly ash, 15 to 60 parts of mechanically activated kaolin, 8 to 40 parts of red mud, 0.5 to 2 parts of a surface modifier, 10 to 35 parts of an acid activator, and 10 to 35 parts of a solvent.
[0007] In the above technical solution, the surface modifier includes at least one of polyethylene glycol, hexadecyltrimethylammonium bromide, ethylenediaminetetraacetic acid, and ethoxysilane.
[0008] In the above technical solution, the preparation method of the mechanically activated kaolin is:
[0009] Put kaolin and zirconia balls into a ball mill, the mass ratio of zirconia balls to kaolin is (5-20):1, the rotation speed is 300-1500r / min, and the grinding time is 30-300min, so as to obtain the mechanically activated kaolin.
[0010] In the above technical solution, the red mud is Bayer process red mud, the mass fraction of Fe2O3 in the red mud is not less than 15%, and the particle size D50 is 40-60 um.
[0011] In the above technical solution, the fly ash is Class F fly ash, and the particle size D50 is 20 to 30 um.
[0012] In the above technical solution, the particle size D50 of the mechanically activated kaolin is 4.00-7.00 um.
[0013] In the above technical solution, the acid activator is a mixture of phosphoric acid and acetic acid, the concentration of acetic acid is 1-5 mol / L, the concentration of phosphoric acid is 5-9 mol / L, and the mass ratio of phosphoric acid to acetic acid is (7-13):1.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned geopolymer, comprising the following steps:
[0015] S1: uniformly mixing the fly ash, mechanically activated kaolin, surface modifier and red mud to obtain a mixture 1;
[0016] S2: The mixed material 1 is uniformly mixed with an acid activator and a solvent, and the mixed material 1 is cured and formed to obtain the geopolymer.
[0017] In the above technical solution, the curing temperature is 20-30°C and the curing time is 16-38h.
[0018] The present invention utilizes the synergistic effect of fly ash, red mud and mechanically activated kaolin, as well as the application of surface modifiers, to significantly optimize the interaction of these industrial byproducts in geopolymers, thereby significantly improving the performance of the final product. This method not only enhances the structure and durability of geopolymers, but also achieves a significant reduction in production costs and efficient resource utilization of bulk solid waste by using a variety of solid waste materials as precursors.
[0019] In addition, the present invention overcomes the limitations of traditional fly ash as a concrete admixture, expands its application scope in building materials, environmental remediation and other fields, reduces dependence on natural resources and the complexity of the production process, and provides a new path for sustainable road construction, foundation reinforcement, and environmental remediation.
[0020] The mechanically activated kaolin modified fly ash phosphate-based polymer of the present invention exhibits an early compressive strength of more than 20 MPa at 3 days, and the compressive strength is further increased to more than 35 MPa at 14 days. Compared with the traditional single fly ash phosphoric acid-activated geopolymer, its net slurry compressive strength is increased by 4.5-6 times. The principles of this significant improvement include:
[0021] (1) Mechanical activation of Al in kaolin and fly ash 3+ With PO4 in phosphoric acid 3- The reaction forms AlPO4 gel. The rapid formation of this gel is the key mechanism to achieve early strength of geopolymer.
[0022] (2) The alkaline environment provided by red mud promotes the dissolution of more silicon (Si) and aluminum (Al) from fly ash and mechanically activated kaolin, increasing the availability and reaction potential of these active components, thereby enhancing the structure and properties of the materials.
[0023] (3) The iron oxides in the red mud participate in the reaction to form a Fe-OP chain structure, which not only enhances the structural integrity of the material but also improves its overall stability and connectivity, thereby enhancing the durability and compressive resistance of the geopolymer.
[0024] (4) Surface modifiers enhance the bonding between particles by improving the surface properties of fly ash and other solid components. This enhanced bonding effectively reduces the erosion of water on the geopolymer structure and further improves the stability and durability of the material.
[0025] These combined effects ensure that the geopolymer exhibits high compressive strength at an early stage and its performance continues to increase with the extension of curing time.
[0026] The mechanically activated kaolin modified fly ash phosphate-based polymer of the present invention has no shrinkage in the later stage, and the strength after 90 days reaches 50-65 MPa, which is 4.8 to 6.5 times of the single fly ash phosphate-activated geopolymer, and also significantly exceeds the compressive strength of the metakaolin modified fly ash phosphate-based polymer by 2.0 to 3.5 times. This significant increase in strength is due to the rich silicon (Si) and aluminum (Al) sources provided by the mechanically activated kaolin, which promotes the formation of complex aluminum phosphate silicates (Si-O-Al-OP, Al-OP) in a phosphoric acid environment. The formation of these structures not only stabilizes the microstructure of the geopolymer, but also inhibits the generation of low-strength Si-OP products, ensuring the high performance and long-term stability of the material. The fly ash spherical particles reduce the agglomeration of the mechanically activated kaolin lamellae, promote the dissolution of Si and Al, and further increase the density and uniformity of the geopolymer, which is particularly important for improving the compressive strength of the material.
[0027] The present invention solves the limitation that fly ash has too low early strength in phosphate-based polymers and can only be used as an additive in traditional applications. The present invention not only greatly improves the utilization rate of large solid wastes such as fly ash and red mud, but also significantly reduces the potential risk of heavy metals (such as Pb, Zn, etc.) contained therein as environmental pollution sources, while reducing the cost of environmental governance and waste treatment.
[0028] The mechanical activation of kaolin in the present invention promotes the reaction of more silicates and aluminates in fly ash to form complex aluminum phosphate silicate (Si-O-Al-OP, Al-OP) structures, which provide higher material compressive strength and durability. At the same time, compared with traditional calcined kaolin treatment, the mechanical activation process greatly reduces energy consumption and carbon emissions, providing an environmentally friendly material treatment method.
[0029] In addition, the mechanically activated kaolin-modified fly ash phosphate-based polymer of the present invention has strong freeze-thaw resistance, dry-wet resistance, brine erosion resistance and carbonization resistance, making it an ideal building material suitable for a variety of extreme environmental conditions.
[0030] The beneficial effects of the present invention are:
[0031] The present invention enhances the activity of fly ash and improves its utilization rate in geopolymerization reaction by adopting acid activation technology, so that fly ash is converted into a structural material with high early strength, low early strength and low reaction activity. Compared with the prior art, fly ash is usually used in the form of landfill or simple concrete filler, resulting in a large amount of resources not being fully utilized. The application scope of fly ash is effectively expanded and its economic value is improved.
[0032] The present invention adopts mechanically activated kaolin, which not only saves energy consumption caused by high-temperature calcination, but also significantly reduces CO2 emissions. Compared with the prior art, metakaolin is treated by calcining kaolin to improve its activity, resulting in higher energy consumption and more carbon emissions. Mechanically activated kaolin can provide higher compressive strength than traditional metakaolin, because mechanical activation can more effectively increase the specific surface area and reaction activity of the material, thereby improving the performance of the geopolymer product.
[0033] The present invention adopts an acid excitation liquid (a mixture of phosphoric acid and acetic acid), does not require other complicated dissolution steps, significantly simplifies the preparation process, and reduces production costs. Compared with the prior art, alkali excitation often involves dissolving solid powder in liquid, the operation process is complicated and the cost is high. In addition, the acid excitation method avoids possible environmental and safety issues in alkali excitation, and improves the environmental protection and economy of the entire production process.
[0034] The present invention achieves an optimized P / (Al+Si) ratio by precisely controlling the mixing ratio of acetic acid and phosphoric acid, maintaining the chemical balance of the reaction, and thus promoting the effective dissolution of silicon and aluminum. Compared with the prior art, the acid activator is usually single, which may lead to uneven reaction rate or improper control. This control strategy not only accelerates the release rate of useful components, but also ensures the uniform progress of the geopolymerization reaction by adjusting the reaction rate, thereby improving the overall quality and performance of the product.
[0035] In the present invention, the addition of red mud not only promotes the dissolution of Si in fly ash and mechanically activated kaolin under acidic conditions, while the alkaline components of red mud are more conducive to the release of silicon in this environment, but also enhances the density of the geopolymer product by providing additional iron elements, forming a more stable and uniform structure.
[0036] The present invention does not require high-temperature curing, which reduces energy consumption and environmental impact. Compared with the prior art, acid-activated geopolymers require high-temperature curing to achieve suitable material properties. At the same time, the compressive strength at 28 days can reach 43.7MPa, reaching GB / T50081-2019 "Concrete Physical and Mechanical Properties Test Method Standard". It even exceeds the standard of 425 grade cement, providing a wider range of practical application possibilities, especially suitable for the fields of construction and infrastructure. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a flow chart of the method for preparing the mechanically activated kaolin-modified fly ash phosphate-based polymer of the present invention;
[0038] Figure 2 This is a flow chart of the method for preparing a mechanically activated kaolin-modified fly ash phosphate-based polymer according to Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.
[0040] The invention discloses a mechanically activated kaolin modified fly ash phosphate-based geopolymer, which is made of the following raw materials in parts by weight: 30-75 parts of fly ash, 15-60 parts of mechanically activated kaolin, 8-40 parts of red mud, 0.5-2 parts of surface modifier, 10-35 parts of acid activator, and 10-35 parts of solvent. These raw materials and their proportions ensure that the geopolymer has higher compressive strength.
[0041] Preferably, the raw materials for preparing the geopolymer include, by weight, 35-70 parts of fly ash, 25-55 parts of mechanically activated kaolin, 10-30 parts of red mud, 0.5-1.5 parts of surface modifier, 20-35 parts of acid-activated liquid, and 20-35 parts of solvent.
[0042] In the present invention, the preparation method of mechanically activated kaolin is: put kaolin and zirconia balls into a ball mill, the mass ratio of zirconia balls to kaolin is (5-20):1, the rotation speed is 300-1500r / min, and the grinding time is 30-300min, so as to obtain mechanically activated kaolin.
[0043] Preferably, the ball mill speed is 500-1300 r / min, the grinding time is 60-240 min, and the mass ratio of zirconia balls to kaolin is 8-18:1.
[0044] Preferably, the ball mill speed is 1000 r / min, the grinding time is 80 min, and the mass ratio of zirconia balls to kaolin is 15:1.
[0045] In kaolin treated with mechanical activation, the coordination environment of aluminum has changed. The aluminum that originally existed mainly in the form of hexacoordination has partially changed to tetracoordination or pentacoordination. This coordination change can be 27 Al solid-state NMR technology confirmed that the particle size D50 of mechanically activated kaolin is 4.00-7.00um. The mechanical activation method not only improves the chemical activity of kaolin, but also significantly reduces energy consumption and carbon dioxide release compared to calcination treatment.
[0046] In the present invention, the surface modifier includes at least one of polyethylene glycol, hexadecyltrimethylammonium bromide, ethylenediaminetetraacetic acid, and ethoxysilane.
[0047] The red mud is Bayer process red mud, the mass fraction of Fe2O3 in the red mud is not less than 15%, and the particle size D50 is 40-60um.
[0048] The fly ash is Class F fly ash, and the particle size D50 is 20-30um.
[0049] The acid activator is a mixture of phosphoric acid and acetic acid. By introducing acetic acid, the concentration of -COOH in the system increases, the acidic environment becomes milder, the dissolution rate of Si and Al becomes uniform, and the dissolution amount increases. Since -COOH forms a flexible complex with Si and Al, it is more evenly distributed in the reaction solution, the number of geopolymer products increases, and the compressive strength also increases accordingly.
[0050] The concentration of acetic acid is 1-5 mol / L, and the concentration of phosphoric acid is 5-9 mol / L. Preferably, the concentration of acetic acid is 3.5 mol / L; and the concentration of phosphoric acid is 7 mol / L.
[0051] The mass ratio of phosphoric acid to acetic acid is (7-13):1. Within this ratio range, the mechanically activated kaolin modified fly ash phosphoric acid-based polymer has higher compressive strength. The preferred ratio is 11:1.
[0052] The solvent can be water or deionized water.
[0053] The present invention also discloses a method for preparing a mechanically activated kaolin-modified fly ash phosphate-based polymer, comprising the following steps:
[0054] S1: fly ash, mechanically activated kaolin, surface modifier and red mud are uniformly mixed to obtain mixture 1;
[0055] S2: Mix the mixture 1, the acid activator and the solvent evenly, and cure and shape them to obtain a geopolymer.
[0056] In the present invention, the molding method is vibration molding.
[0057] In the present invention, the curing temperature is 20-30° C., and the curing time is 16-38 hours.
[0058] The preparation method of the present invention introduces red mud and mechanically activated kaolin as optimized precursors. The structure of the mechanically activated kaolin is transformed from layered crystals to a more active amorphous structure, which significantly increases the specific surface area and chemical activity. When combined with fly ash, the complementary effect of the two significantly improves the overall reactivity and cementing ability of the geopolymer, thereby enhancing the early and long-term stability of the material. In addition, the alkaline properties of red mud help promote the dissolution of silicon and aluminum in fly ash, and the iron oxides it contains can enhance the density and durability of the material.
[0059] The present invention not only optimizes the performance of geopolymer and improves its early and final compressive strength, but also reduces the preparation cost, energy consumption and environmental impact through the synergistic effect of red mud and mechanically activated kaolin, and provides a new way for the resource utilization of fly ash and other industrial by-products.
[0060] The mechanically activated kaolin-modified fly ash phosphate-based polymer of the present invention is suitable for various civil engineering projects such as road construction, foundation reinforcement, and environmental restoration due to its excellent mechanical properties, excellent durability and environmental adaptability, and meets the needs of sustainable development.
[0061] This will be explained below through a specific implementation plan and product test results.
[0062] Example 1
[0063] The mechanically activated kaolin-modified fly ash phosphate-based polymer of the embodiment of the present invention is obtained by the following preparation method, comprising the following steps:
[0064] S1: First, kaolin, fly ash and red mud are placed in an oven for drying respectively until the mass no longer changes, and then cooled to room temperature to obtain dried kaolin, fly ash and red mud;
[0065] S2: putting the dried kaolin into a ball mill for ball milling at a speed of 1000 r / min and a grinding time of 80 min to obtain a mechanically activated kaolin powder 1;
[0066] S3: 40 parts of mechanically activated kaolin powder, 50 parts of fly ash, 10 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide were placed in a stirrer and stirred for 25 minutes to obtain a mixture 1 for later use;
[0067] S4: 30 parts of an acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) and 30 parts of water are placed in a magnetic stirrer and stirred for 24 hours to obtain a mixed stimulating agent solution 1 for standby use;
[0068] S5: adding the mixed activator solution 1 to the mixture 1 and stirring with a stirrer for 8 minutes to obtain a mechanically activated kaolin-modified fly ash phosphate-based polymer slurry;
[0069] S6: Pour the slurry into a 20mm×20mm×20mm six-link mold for vibration molding, and place it in a 25°C oven for curing for 12 hours to obtain a solidified geopolymer.
[0070] The geopolymer obtained by the method has a 28-day compressive strength of 43.7 MPa and a 90-day compressive strength of 65 MPa.
[0071] Example 2
[0072] The mechanically activated kaolin-modified fly ash phosphate-based polymer of the embodiment of the present invention is obtained by the following preparation method, comprising the following steps:
[0073] S1: First, kaolin, fly ash and red mud are placed in an oven for drying respectively until the mass no longer changes, and then cooled to room temperature to obtain dried kaolin, fly ash and red mud;
[0074] S2: putting the dried kaolin into a ball mill for ball milling at a speed of 800 r / min and a grinding time of 100 min to obtain a mechanically activated kaolin powder 1;
[0075] S3: 45 parts of mechanically activated kaolin powder, 35 parts of fly ash, 20 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide were placed in a stirrer and stirred for 25 minutes to obtain a mixture 1 for later use;
[0076] S4: 30 parts of an acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) and 30 parts of water are placed in a magnetic stirrer and stirred for 24 hours to obtain a mixed stimulating agent solution 1 for standby use;
[0077] S5: adding the mixed activator solution 1 to the mixture 1 and stirring with a stirrer for 8 minutes to obtain a mechanically activated kaolin-modified fly ash phosphate-based polymer slurry;
[0078] S6: Pour the slurry into a 20mm×20mm×20mm six-link mold for vibration molding, and place it in a 25°C oven for curing for 12 hours to obtain a solidified geopolymer.
[0079] The geopolymer obtained by the method has a 28-day compressive strength of 39 MPa and a 90-day compressive strength of 43 MPa.
[0080] Example 3
[0081] The mechanically activated kaolin-modified fly ash phosphate-based polymer of the embodiment of the present invention is obtained by the following preparation method, comprising the following steps:
[0082] S1: First, kaolin, fly ash and red mud are placed in an oven for drying respectively until the mass no longer changes, and then cooled to room temperature to obtain dried kaolin, fly ash and red mud;
[0083] S2: putting the dried kaolin into a ball mill for ball milling at a speed of 600 r / min and a grinding time of 120 min to obtain a mechanically activated kaolin powder 1;
[0084] S3: 30 parts of mechanically activated kaolin powder, 60 parts of fly ash, 10 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide were placed in a stirrer and stirred for 25 minutes to obtain a mixture 1 for later use;
[0085] S4: 30 parts of an acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) and 30 parts of water are placed in a magnetic stirrer and stirred for 24 hours to obtain a mixed stimulating agent solution 1 for standby use;
[0086] S5: adding the mixed activator solution 1 to the mixture 1 and stirring with a stirrer for 8 minutes to obtain a mechanically activated kaolin-modified fly ash phosphate-based polymer slurry;
[0087] S6: Pour the slurry into a 20mm×20mm×20mm six-link mold for vibration molding, and place it in a 25°C oven for curing for 12 hours to obtain a solidified geopolymer.
[0088] The geopolymer obtained by the method has a 28-day compressive strength of 35 MPa and a 90-day compressive strength of 38 MPa.
[0089] Example 4
[0090] The mechanically activated kaolin-modified fly ash phosphate-based polymer of the embodiment of the present invention is obtained by the following preparation method, comprising the following steps:
[0091] S1: First, kaolin, fly ash and red mud are placed in an oven for drying respectively until the mass no longer changes, and then cooled to room temperature to obtain dried kaolin, fly ash and red mud;
[0092] S2: putting the dried kaolin into a ball mill for ball milling at a speed of 1200 r / min and a grinding time of 180 min to obtain a mechanically activated kaolin powder 1;
[0093] S3: 30 parts of mechanically activated kaolin powder, 50 parts of fly ash, 20 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide were placed in a stirrer and stirred for 25 minutes to obtain a mixture 1 for later use;
[0094] S4: 30 parts of an acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) and 30 parts of water are placed in a magnetic stirrer and stirred for 24 hours to obtain a mixed stimulating agent solution 1 for standby use;
[0095] S5: adding the mixed activator solution 1 to the mixture 1 and stirring with a stirrer for 8 minutes to obtain a mechanically activated kaolin-modified fly ash phosphate-based polymer slurry;
[0096] S6: Pour the slurry into a 20mm×20mm×20mm six-link mold for vibration molding, and place it in a 25°C oven for curing for 12 hours to obtain a solidified geopolymer.
[0097] The geopolymer obtained by the method has a 28-day compressive strength of 29 MPa and a 90-day compressive strength of 34 MPa.
[0098] Example 5
[0099] The mechanically activated kaolin-modified fly ash phosphate-based polymer of the embodiment of the present invention is obtained by the following preparation method, comprising the following steps:
[0100] S1: First, kaolin, fly ash and red mud are placed in an oven for drying respectively until the mass no longer changes, and then cooled to room temperature to obtain dried kaolin, fly ash and red mud;
[0101] S2: putting the dried kaolin into a ball mill for ball milling at a speed of 900 r / min and a grinding time of 80 min to obtain a mechanically activated kaolin powder 1;
[0102] S3: 20 parts of mechanically activated kaolin powder, 50 parts of fly ash, 30 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide were placed in a stirrer and stirred for 25 minutes to obtain a mixture 1 for later use;
[0103] S4: 30 parts of an acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) and 30 parts of water are placed in a magnetic stirrer and stirred for 24 hours to obtain a mixed stimulating agent solution 1 for standby use;
[0104] S5: adding the mixed activator solution 1 to the mixture 1 and stirring with a stirrer for 8 minutes to obtain a mechanically activated kaolin-modified fly ash phosphate-based polymer slurry;
[0105] S6: Pour the slurry into a 20mm×20mm×20mm six-link mold for vibration molding, and place it in a 25°C oven for curing for 12 hours to obtain a solidified geopolymer.
[0106] The geopolymer obtained by the method has a 28-day compressive strength of 23 MPa and a 90-day compressive strength of 30 MPa.
[0107] Comparative Example 1
[0108] The 40 parts of mechanically activated kaolin powder, 50 parts of fly ash, 10 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide in Example 1 are replaced with 50 parts of mechanically activated kaolin powder, 50 parts of fly ash, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide, and the remaining steps are the same as in Example 1.
[0109] The 28-day compressive strength of the geopolymer obtained in Comparative Example 1 is 22 MPa, and the 90-day compressive strength is 35 MPa. Compared with Example 1, the 28-day strength is reduced by about 20 MPa, and the 90-day strength is reduced by about 30 MPa. The reason is that the solubility of Si in fly ash and mechanically activated kaolin under alkaline conditions is greater than that under acidic conditions. The lack of red mud leads to a decrease in the Si / Al ratio of the geopolymer, which makes the generated geopolymer product have poor structural stability, and low-concentration Si(OH)4 (the dissolved form of SiO2) is relatively stable and difficult to participate in the geopolymerization reaction, which ultimately leads to a decrease in the compressive strength of the geopolymer product.
[0110] Comparative Example 2
[0111] The 40 parts of mechanically activated kaolin powder, 50 parts of fly ash, 10 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide in Example 1 are replaced with 50 parts of fly ash, 50 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide, and the remaining steps are the same as in Example 1.
[0112] The compressive strength of the geopolymer obtained in Comparative Example 2 was 15 MPa at 28 days and 18 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 28 MPa and the strength at 90 days decreased by about 47 MPa. The reasons are as follows: fly ash has a low activity, which leads to a decrease in the effective utilization rate of silicon and aluminum elements, and part of the acid activator participating in the geopolymerization reaction is consumed by red mud, resulting in an incomplete geopolymerization reaction, with more unreacted or partially reacted areas, and ultimately resulting in a decrease in the compressive strength of the geopolymer product.
[0113] Comparative Example 3
[0114] The 40 parts of mechanically activated kaolin powder, 50 parts of fly ash, 10 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide in Example 1 were replaced with 50 parts of mechanically activated kaolin, 50 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide, and the remaining steps were the same as in Example 1.
[0115] The compressive strength of the geopolymer obtained in Comparative Example 3 was 19 MPa at 28 days and 26 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 25 MPa and the strength at 90 days decreased by about 39 MPa. The reasons are as follows: the active Al in the mechanically activated kaolin cannot fully participate in the geopolymerization reaction but exists in the form of unreacted particles, the lamellar structure of the metakaolin increases in agglomeration due to the lack of the spherical structure of the fly ash, the acid activator participating in the geopolymerization reaction decreases due to the consumption of red mud, resulting in incomplete geopolymerization reaction, and ultimately resulting in a decrease in the compressive strength of the geopolymer product.
[0116] Comparative Example 4
[0117] The 30 parts of acid stimulating solution (mixed by 2 parts of 3.5 mol / L acetic acid and 28 parts of 7 mol / L phosphoric acid) in Example 1 were replaced with 30 parts of 7 mol / L phosphoric acid, and the remaining steps were the same as in Example 1.
[0118] The compressive strength of the geopolymer obtained in Comparative Example 4 was 25 MPa at 28 days and 42 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 19 MPa and the strength at 90 days decreased by about 23 MPa. The reasons are as follows: the amount of dissolved Si and Al in mechanically activated kaolin, fly ash and red mud decreased, resulting in a decrease in the products participating in the geopolymerization reaction. On the other hand, the rate of dissolution of Si and Al in the system was too fast, and the geopolymerization reaction rate was too fast, resulting in uneven distribution of geopolymer products, increasing the porosity and unevenness of the structure, and ultimately reducing the compressive strength.
[0119] Comparative Example 5
[0120] The 30 parts of acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) in Example 1 were replaced with 30 parts of acid stimulating solution (mixed by 12 parts of acetic acid with a concentration of 5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L), and the remaining steps were the same as in Example 1.
[0121] The compressive strength of the geopolymer obtained in Comparative Example 5 is 30 MPa at 28 days and 45 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 14 MPa, and the strength at 90 days decreased by about 20 MPa. The reasons are: the amount and rate of Al dissolution decreased, the amount of phosphoaluminosilicate products generated decreased, resulting in increased brittleness of the geopolymer reaction product, and the geopolymer reaction decreased due to the increase in the pH of the system, resulting in a decrease in the amount of products generated by the geopolymer reaction and an increase in the porosity of the system, which ultimately led to a decrease in the compressive strength of the geopolymer product.
[0122] Comparative Example 6
[0123] The 30 parts of acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 7 mol / L) in Example 1 were replaced with 30 parts of acid stimulating solution (mixed by 2 parts of acetic acid with a concentration of 3.5 mol / L and 28 parts of phosphoric acid with a concentration of 9 mol / L), and the remaining steps were the same as in Example 1.
[0124] The compressive strength of the cementitious material obtained in Comparative Example 6 was 32 MPa at 28 days and 49 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 12 MPa and the strength at 90 days decreased by about 16 MPa. The reason is that as the concentration of phosphoric acid increases, the excess H2PO4 in the system - PO4 3- With Al 3+ The reaction is more intense, forming aluminum phosphate precipitation. Due to the consumption of aluminum-oxygen tetrahedrons, the amount of silicon-aluminum phosphate generated by the geopolymerization reaction is reduced, resulting in a decrease in the structural integrity and performance of the geopolymer product, and ultimately a decrease in the compressive strength of the geopolymer product.
[0125] Comparative Example 7
[0126] The rotation speed of the ball mill in Example 1 was 1000 r / min and the grinding time was 80 min. The rotation speed was 1200 r / min and the grinding time was 80 min. The remaining steps were the same as in Example 1.
[0127] The compressive strength of the geopolymer obtained in Comparative Example 7 was 39 MPa at 28 days and 56 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 5 MPa and the strength at 90 days decreased by about 9 MPa. The reason is that as the rotation speed increases, the mechanically activated kaolin agglomerates. The reaction sites provided by the agglomerated mechanically activated kaolin decrease, resulting in a decrease in dissolved Al and silicon elements, a decrease in the geopolymer reaction product formed, and ultimately a decrease in the compressive strength of the geopolymer product.
[0128] Comparative Example 8
[0129] The rotation speed of the ball mill in Example 1 was 1000 r / min and the grinding time was 80 min. The rotation speed was 1000 r / min and the grinding time was 120 min. The remaining steps were the same as in Example 1.
[0130] The compressive strength of the geopolymer obtained in Comparative Example 8 was 29 MPa at 28 days and 38 MPa at 90 days. Compared with Example 1, the 28-day strength decreased by about 15 MPa and the 90-day strength decreased by about 27 MPa. The reason is that as the grinding time increases, the particle size of the mechanically activated kaolin is too small and agglomerated, which reduces the effective reaction area and dispersibility, and the amount of geopolymer reaction products formed is reduced, which ultimately leads to a decrease in the compressive strength of the geopolymer product.
[0131] Comparative Example 9
[0132] The 40 parts of mechanically activated kaolin powder, 50 parts of fly ash, 10 parts of red mud, 0.9 parts of polyethylene glycol, and 0.6 parts of cetyltrimethylammonium bromide in Example 1 are replaced with 40 parts of mechanically activated kaolin powder, 50 parts of fly ash, and 10 parts of red mud, and the remaining steps are the same as Example 1.
[0133] The compressive strength of the geopolymer obtained in Comparative Example 9 was 36 MPa at 28 days and 51 MPa at 90 days. Compared with Example 1, the strength at 28 days decreased by about 8 MPa and the strength at 90 days decreased by about 14 MPa. The reasons are: the dissolution rate of Si and aluminum is uneven, the dispersibility of dissolved silicon oxygen tetrahedrons and aluminum oxygen tetrahedrons and octahedrons is reduced, resulting in an excessively fast and uneven geopolymerization reaction rate, a reduction in the number and uniformity of the geopolymerization reaction products formed, and ultimately a decrease in the compressive strength of the geopolymer products.
[0134] Table 1 Compressive strength of materials at different ages, MPa
[0135] Group 28d compressive strength 90d compressive strength Example 1 43.7 65.0 Example 2 39 43 Example 3 35 38 Example 4 29 34 Example 5 23 30 Comparative Example 1 22 35 Comparative Example 2 15 18 Comparative Example 3 19 26 Comparative Example 4 25 42 Comparative Example 5 30 45 Comparative Example 6 32 49 Comparative Example 7 39 56 Comparative Example 8 29 38 Comparative Example 9 36 51
[0136] It can be seen from the above table that the 28-day compressive strength and 90-day compressive strength of the geopolymers prepared in Examples 1-5 of the present invention are better than those in Comparative Examples 1-9. The geopolymers of the present invention are suitable for various civil engineering projects such as road construction, foundation reinforcement, and environmental restoration due to their excellent mechanical properties, excellent durability, and environmental adaptability, and meet the needs of sustainable development.
[0137] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A mechanically activated kaolin-modified fly ash phosphate-based polymer, characterized in that: The geopolymer is prepared from the following raw materials in parts by weight: 30-75 parts of fly ash, 15-60 parts of mechanically activated kaolin, 8-40 parts of red mud, 0.5-2 parts of surface modifier, 10-35 parts of acid activator and 10-35 parts of solvent.
2. The geopolymer according to claim 1, characterized in that: The surface modifier includes at least one of polyethylene glycol, hexadecyltrimethylammonium bromide, ethylenediaminetetraacetic acid, and ethoxysilane.
3. The geopolymer according to claim 1, characterized in that: The preparation method of the mechanically activated kaolin is: Put kaolin and zirconia balls into a ball mill, the mass ratio of zirconia balls to kaolin is (5-20):1, the rotation speed is 300-1500r / min, and the grinding time is 30-300min, so as to obtain the mechanically activated kaolin.
4. The geopolymer according to claim 1, characterized in that: The red mud is Bayer red mud, the mass fraction of Fe2O3 in the red mud is not less than 15%, and the particle size D50 is 40-60 um.
5. The geopolymer according to claim 1, characterized in that: The fly ash is Class F fly ash, and the particle size D50 is 20-30 um.
6. The geopolymer according to claim 3, characterized in that: The particle size D50 of the mechanically activated kaolin is 4.00-7.00 um.
7. The geopolymer according to claim 1, characterized in that: The acid activator is a mixture of phosphoric acid and acetic acid, the concentration of acetic acid is 1-5 mol / L, the concentration of phosphoric acid is 5-9 mol / L, and the mass ratio of phosphoric acid to acetic acid is (7-13):
1.
8. The method for preparing the geopolymer according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: uniformly mixing the fly ash, mechanically activated kaolin, surface modifier and red mud to obtain a mixture 1; S2: The mixed material 1 is uniformly mixed with an acid activator and a solvent, and the mixed material 1 is cured and formed to obtain the geopolymer.
9. The preparation method according to claim 8, characterized in that: The curing temperature is 20-30℃, and the curing time is 16-38h.
Citation Information
Patent Citations
Geopolymer composition, geopolymer material and preparation method of geopolymer material
CN104098282A
Geopolymer cementitious material and preparation method thereof
CN104150792A
Layered kaolin material as well as preparation method and application thereof
CN115322611A
Phosphoric acid-based geopolymer semi-rigid base material and application thereof
CN116750995A
Charge distribution method of charger of electric vehicle based on artificial intelligence
KR102746222B1
Cited By
Anti-cracking phosphoric acid-based geopolymer, anti-cracking recycled aggregate, and preparation method and application of anti-cracking phosphoric acid-based geopolymer and anti-cracking recycled aggregate
CN121362005A